Pengaruh Pembiayaan Murabahah, Pembiayaan Mudharabah dan Pembiayaan Musyarakah Terhadap Profitabilitas - Citra Intan Purnama Sari; Sulaeman Sulaeman (Al Maal: Journal of Islamic Economics and Banking, 2021)
This study aims to determine the effect of murabahah financing, mudharabah financing and musyarakah financing on the level of profitability. This research was conducted using quantitative methods with an associative approach. The object of this research is the three Sharia Commercial Bank financial statements for the period 2016-2019 as many as three Islamic Commercial Banks and a sample of 48 financial reports. In this study, sampling was using purposive sampling technique. Data collection techniques using secondary data. The data analysis technique used is the classical assumption test, multiple linear analysis, and hypothesis testing. The results of this study indicate that murabahah financing has a positive effect on ROA with a significant level of 0.000. Mudharabah financing has a positive effect on ROA with a significant level of 0.000. Meanwhile, musyarakah financing has no positive effect on ROA with a significance level of 0.000. Meanwhile, simultaneously Murabahah Financing, Mudharabah Financing and Musharaka Financing have an effect of 91% on the level of Profitability at Islamic Commercial Banks in Indonesia for the period 2016-2019, the remaining 9% is influenced by other factors not examined by the authors in this study